2014
DOI: 10.1016/j.molcata.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde adsorption and condensation on anatase TiO2: Influence of acetaldehyde dimerization

Abstract: Conversion of acetaldehyde to crotonaldehyde on anatase TiO 2 films was studied by in situ Fourier transform infrared spectroscopy (FTIR) and by density functional theory (DFT) calculations. In situ FTIR showed that acetaldehyde adsorption is accompanied by the appearance of a hitherto nonassigned absorption band at 1643 cm -1 , which is shown to be due to acetaldehyde dimers. The results were supported by DFT calculations. Vibrational frequencies calculated within a partially relaxed cluster model for molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 47 publications
6
34
0
Order By: Relevance
“…[63][64][65] Previous studies of the vapor phase aldol condensation of acetaldehyde have reported the active 2-butenal-forming site to be a medium-strength, M-O-type site. 19,23,65,66 Tolualdehydes (ortho-and para-) can form through 2 main routes. 12 The first route involves a cascade reaction: acetaldehyde self-condenses to its dimer, 2-butenal.…”
Section: Aromatics Production From Acetaldehyde Over Mg X Al-ox and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65] Previous studies of the vapor phase aldol condensation of acetaldehyde have reported the active 2-butenal-forming site to be a medium-strength, M-O-type site. 19,23,65,66 Tolualdehydes (ortho-and para-) can form through 2 main routes. 12 The first route involves a cascade reaction: acetaldehyde self-condenses to its dimer, 2-butenal.…”
Section: Aromatics Production From Acetaldehyde Over Mg X Al-ox and Mmentioning
confidence: 99%
“…Lewis acid centers like those generated by Al 3+ substitution in MgO are known to act as adsorption sites for electron-donating carbonyl oxgyens. 66,75,76 Previous studies 30,[34][35][36][37][38] have reported that acid sites can facilitate the nucleophilic attack (e.g., in an aldol mechanism) by increasing the electrophilicity of the carbonyl-C bonded to a carbonyl-O adsorbed on an acid site. However, activation of the carbonyl-C of the neutral 2-butenal via the Al 3+ -carbonyl-O interaction would not likely impact the isomeric selectivity in routes 2A and 2B, since increased electrophilicity of the carbonyl-C would not necessarily favor one route over the other (they have the same electrophile).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Formaldehyde (HCHO) and acetaldehyde (CH 3 CHO) are considered two of the most important aldehydes [7,8]. They are known as carcinogenic and probably carcinogenic agents, respectively [9,10]. Acetaldehyde is also a highly toxic compound [18].…”
Section: Introductionmentioning
confidence: 99%
“…Solar photocatalytic oxidation processes for water and air pollutants degradation have received increasing attention as they are aiming at completely destroying the pollutants, as compared to most of the traditional processes that actually concentrate the pollutants in a separate phase, without eliminating them. Usually, air decontamination focuses on SO x , NO x and organic VOCs as main contributors to the greenhouse effect; however, acetaldehyde raises interest when analysing indoor pollution [1][2][3], as it can be released by some construction materials such as polyurethane foams, and consumer products such as cigarettes, adhesives, coatings and inks [4]. Short term inhalation of acetaldehyde affects the human respiratory system while direct contact irritates the skin and eyes; additionally, acetaldehyde can adversely affect the cardiovascular system and it has been anticipated to be a human carcinogen [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of different mono-component photocatalyst such as TiO 2 [7][8][9], ZnO [10,11], SnO 2 [12,13] or WO 3 [14,15] demonstrated the feasibility of using a semiconductor to reduce the air pollutants content. Although efficient, these materials have limited response under Vis/solar irradiation, with negative consequences considering sustainability (energy consumption) and the overall cost of the photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%